Composite Flours Based on Black Lentil Seeds and Sprouts with Nutritional, Phytochemical and Rheological Impact on Bakery/Pastry Products - Christine (Neagu) Dragomir; Sylvestre Dossa; Călin Jianu; Ileana Cocan; Isidora Radulov; Adina Berbecea; Florina Radu; Ersilia Alexa (Foods)
This paper aimed to study the nutritional, phytochemical and rheological properties of some composite flours based on wheat flour (WF) mixed with non-germinated (LF) and sprouted lentil flour (SLF), in order to fortify the wheat flour and to obtain functional bakery/pastry products. The composite flours based on wheat flour and bean lentil flour (BLWF) and sprouted lentil flour (SLWF) were analyzed from the point of view of proximate composition (proteins, lipids, total carbohydrates, and minerals), content of individual and total polyphenols (TPC), as well as the contents of macro and microelements. For use in baking/pastries, the composite flours were tested from the point of view of rheological behavior using the MIXOLAB system, and the profiles obtained were compared with those of bread and biscuit. The results indicated that fortifying wheat flour with lentil flour, both in non-germinated and sprouted forms, increased the protein by 0.6–35.2% and mineral content of the samples and decreased the lipids by 8.3–43.2% and the carbohydrates by 2.8–9.4%. The total polyphenol content (TPC) increased by fortifying the wheat flour with non-germinated and sprouted lentil flour, the increase being between 39.2–131.4%. Regarding individual polyphenols, nine polyphenols were determined, of which epicatechin (46.979 mg/kg) and quercetin (45.95 mg/kg) were identified in the highest concentration in the composite flours. The increase in micronutrient intake by fortifying wheat flour with black lentil flour in both germinated and ungerminated form is more significant compared to the increases recorded in the case of the main macronutrients (Ca, Na, Mg, and K). The micronutrients increased in the composite flours in the order: Cu < Zn < Fe < Mn. The MIXOLAB profile highlighted that black lentil flour, although having a higher absorption index than that recommended for biscuit production, would improve the stability of the dough.